Birds of a feather age together: telomere dynamics and social behavior predict life span in female Japanese quail (Coturnix japonica) - McCollum, Shannon E.; Canter, Olivia; Fasanello, Vincent J.; Gronsky, Sarah; Haussmann, Mark F. (Frontiers in Endocrinology, 2024)
Social support is vital for mental and physical health and is linked to lower rates of disease and early mortality. Conversely, anti-social behavior can increase mortality risks, both for the initiator and target of the behavior. Chronic stress, which also can increase mortality, may serve as an important link between social behavior and healthy lifespan. There is a growing body of literature in both humans, and model organisms, that chronic social stress can result in more rapid telomere shortening, a measure of biological aging. Here we examine the role of anti-social behavior and social support on physiological markers of stress and aging in the social Japanese quail, Coturnix Japonica. Birds were maintained in groups for their entire lifespan, and longitudinal measures of antisocial behavior (aggressive agonistic behavior), social support (affiliative behavior), baseline corticosterone, change in telomere length, and lifespan were measured. We found quail in affiliative relationships both committed less and were the targets of less aggression compared to birds who were not in these relationships. In addition, birds displaying affiliative behavior had longer telomeres, and longer lifespans. Our work suggests a novel pathway by which social support may buffer against damage at the cellular level resulting in telomere protection and subsequent longer lifespans.